An Empirical Research About Psycho-Factors In Utilization of Natural Language: Exploring the Relationship Between Word Utilization and Psycho-Factors in Natural Language (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The words people use in their everyday lives can uncovercritical perspectives of their social and psychological worlds. Withdevelopments in computer technology, content analysis permits analysts todependably and rapidly survey characteristics of what people say and inaddition subtleties in their linguistic styles. Accompanying a short survey ofsome content analysis programs, we condense a portion of the proof thatconnections common word utilization to psyche, social and situationalvacillations, and psychological intercessions. Exceptionally compelling are discoveries that indicatethe psychological quality of examining particles—parts of discourse thatincorporate pronouns, articles, prepositions, conjunctives, furthermoreassistant verbs. Particles, which serve as the paste that holds things andgeneral verbs together, can serve as markers of emotional state, socialcharacter, and cognitive styles.